An unusual case of abdominal sepsis following traumatic injury. (5th August 2015) - Ellington, Matt
Abstract : A 19-year-old woman presented to our emergency department with crampy abdominal pain and per rectal bleeding 2 weeks after falling from a horse. She had been taking regular non-steroidal anti-inflammatory drugs (NSAIDs) for analgaesia. On arrival, she was tachycardic and tachypnoeic, with a lactate of 7.3 mmol/L. 'FAST' ultrasonography was unremarkable and CT scan showed thickened wall of the transverse colon. She underwent flexible sigmoidoscopy, which demonstrated "patchy inflammation and an isolated area of severe deep ulceration with nodularity and oedema". A presumptive diagnosis of "Inflammatory Bowel Disease—likely Crohn's", was made, and treated accordingly with steroids and Pentasa. Two months following discharge, the patient underwent a colonoscopy, showing a normal colon, however, "a few ulcers in the terminal ileum" were seen. She was seen by a gastroenterologist who deemed the most likely diagnosis to be NSAID-induced terminal ileitis and colitis. Having stopped the offending NSAID (and steroids), she has now made a full recovery.